ผลการใช้ชุดกิจกรรมการสร้างวินัยเชิงบวกตามแนวคิดการเรียนรู้โปรแอคทีฟ (Pro-Active learning) ที่มีต่อพัฒนาการทางอารมณ์และสังคมของเด็กปฐมวัยในศูนย์พัฒนาเด็กเล็ก สังกัดองค์กรปกครองส่วนท้องถิ่น อำเภอเมือง จังหวัดชัยนาท: The Result of the utilization of the Activity Packages which aims to develop the Positive Discipline Based on Pro-Active Learning on young children’s Emotion Development and Social Development at the Child Development Centers under Local Administration Organizations at the Mueang Chainat District, Chainat Province - Patchara Poompachati, พัชรา พุ่มพชาติ (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2020)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ พัฒนาชุดกิจกรรมการสร้างวินัยเชิงบวกตามแนวคิดการเรียนรู้โปรแอคทีฟ และศึกษาผลการใช้ชุดกิจกรรมการสร้างวินัยเชิงบวกตามแนวคิดการเรียนรู้โปรแอคทีฟที่มีต่อพัฒนาการทางอารมณ์และสังคมของเด็กปฐมวัย เป็นการวิจัยเชิงทดลอง โดยใช้แบบแผนการวิจัยแบบกำหนดกลุ่มควบคุม ทดสอบก่อนและหลังการจัดกิจกรรมต่อเนื่องตามเวลาที่กำหนด (Control-Group Interrupted Time-Series Design) (Creswell. 2003 : 169) กลุ่มตัวอย่างเป็นครูปฐมวัย จำนวน 2 คน และเด็กปฐมวัยกลุ่มทดลอง และกลุ่มควบคุม กลุ่มละ 30 คน รวม 60 คนในศูนย์พัฒนาเด็กเล็ก สังกัดองค์กรปกครองส่วนท้องถิ่น อำเภอเมือง จังหวัดชัยนาท โดยใช้วิธีการสุ่มตัวอย่างแบบหลายขั้นตอน (Multi-Stage Sampling) เครื่องมือวิจัย ประกอบด้วย ชุดกิจกรรม แบบสังเกตพัฒนาการทางอารมณ์สำหรับเด็กปฐมวัย แบบสังเกตพัฒนาการทางสังคมสำหรับเด็กปฐมวัย และ แบบสอบถามความพึงพอใจของครูปฐมวัย สถิติที่ใช้ในการวิเคราะห์ข้อมูล คือ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบค่าทีแบบ Dependent t-test , Independent t-test และการวิเคราะห์เนื้อหา ผลการวิจัยพบว่า (1) ผลการพัฒนาชุดกิจกรรม ประกอบด้วย องค์ประกอบของชุดกิจกรรม คู่มือการใช้ชุดกิจกรรม และคู่มือปฏิบัติกิจกรรม ทุกองค์ประกอบมีค่าดัชนีความสอดคล้องสูงกว่าเกณฑ์ที่กำหนด สามารถนำไปใช้ในการพัฒนาเด็กปฐมวัยได้ (2) ผลการใช้ชุดฝึกชุดกิจกรรม พบว่า 1) พัฒนาการทางอารมณ์และสังคมของเด็กปฐมวัยในกลุ่มทดลองที่ได้รับการจัดกิจกรรม โดยใช้ชุดกิจกรรมสูงกว่าก่อนการจัดกิจกรรม 2) พัฒนาการทางอารมณ์และสังคมของเด็กปฐมวัยในกลุ่มทดลองที่ได้รับการจัดกิจกรรม โดยใช้ชุดกิจกรรมใน 4 ระยะ มีพัฒนาการสูงขึ้นอย่างเป็นลำดับ 3) พัฒนาการทางอารมณ์ และสังคมระหว่างเด็กปฐมวัยในกลุ่มทดลองสูงกว่าเด็กปฐมวัยในกลุ่มควบคุม และ 4) ครูมีความพึงพอใจต่อชุดกิจกรรมอยู่ในระดับมาก This study was aimed to develop the activity packages which aims to develop the Positive Discipline Based on Pro-Active Learning, and 2) examine the influences of using the activity packages on young children’s Emotion Development and Social Development The study employed a control-group interrupted time-series design (Creswell. 2003 : 169), The participants are 2 preschool teachers, 30 pre-primary children in control group and 30 pre-primary children at the Child Development Centers under Local Administration Organizations at the Chainat Province. Multi-Stage Sampling selection was applied. The research tools were an utilization of the Activity Packages, an observation form on Emotion and Social Development to be filled by pre-primary children, and an evaluation form on the satisfaction of teachers. Data analysis was performed through percentage, mean ( ), standard deviation (S.D.), dependent t-test and independent t-test as well as content analysis. To serve the research objectives, the results included two areas. First, the effectiveness of developing this activity packages which consists of the activity package components, the guidebook on how to use the teacher toolkit, and the guidebook on practical use of the toolkit for teacher, the assessment of the relevancy of the activity packages found that all of the relevant indexes are higher than the criteria and was an effective method to develop pre-primary children . Second, after utilizing the activity packages, it is revealed that 1) The pre-primary children whose teachers utilized the activity packages have more emotion and social development after joining this experimental activity as compared to before joining 2) The pre-primary children whose teachers utilized the activity packages continuously and respectively develop higher social development after several experiments which expand over four phases from before the teachers used the toolkit, after they used the toolkit once, after they used the toolkit twice, and after the follow-up period. 3) The pre-primary children in experimental group have more emotion and social development than children in control group 4) the teachers are positive and have high satisfaction towards the activity packages.